Use of cannabis to manage symptoms of mental and physical health conditions during pregnancy: analysis of a pro-cannabis pregnancy forum - Gunn, Rachel L.; Aston, Elizabeth R.; Artis, Lia; Nesi, Jacqueline; Pedersen, Eric R.; Micalizzi, Lauren (Frontiers in Psychiatry, 2024)
IntroductionRates of prenatal cannabis use (PCU) have increased in recent years. Despite evidence of developmental health consequences to offspring and birthing person, there has been a reduction in the perception of PCU-related harms. Due to the stigma and risk of legal consequences associated with disclosing PCU, individuals are often cautious to seek information from their healthcare providers. Thus, pregnant people are more likely to seek information from anonymous sources, such as online support forums. Information garnered from these anonymous online forums can shed light on the patterns and motives for cannabis use among this population. These insights can help to better inform prevention efforts aimed at reducing potential harms of PCU and improve intervention efforts.MethodsPosts (N = 120) from an online pro-cannabis pregnancy forum called “Ganja Mamas” on WhattoExpect.com were randomly selected and analyzed if they covered topics related to PCU. A qualitative coding structure based on the existing PCU literature was created and refined to include other emergent topics. The coding structure was used to apply thematic analysis to posts; associated codes were grouped into themes. Codes specific to symptom management for physical and mental health were subsequently subjected to further conceptual analysis for the current study.ResultsFour themes related to symptom management during pregnancy were identified: 1) cannabis use and impacts of use for a variety of mental health symptoms, including depression and anxiety; 2) cannabis use for physical health symptoms and conditions, such as nausea and pain; 3) use of cannabis to achieve homeostasis and manage stress; 4) decision-making about using cannabis for symptom management, such as using cannabis instead of prescription medications. Most discussions in this pro-cannabis forum reflected perceptions that cannabis was effective in treating the conditions for which it was used; however, limitations of cannabis’ efficacy were also mentioned.DiscussionThere is need for reduced stigma and open communication between pregnant persons who use cannabis and their providers in discussing how to manage their mental and physical health symptoms. Understanding the various symptoms for which individuals use cannabis during pregnancy to self-treat can inform these conversations and the expansion of harm reduction strategies.